Follow me! : creating a personal brand with Twitter - Gratton, Sarah-Jayne (John Wiley & Sons, 2012)
Make the most of Twitter as a tool for creating a personal brand Twitter boasts more than 100 million active users with 50 million of them actively tweeting every day, making Twitter an indisputably powerful marketing platform. With this unique book, author and Twitter guru Sarah-Jayne Gratton offers real-world examples and proven techniques for capturing a Twitter audience and using that audience to spread the word on your personal brand. * Details ways in which you can use Twitter to build a personal brand* Shows you how to maximize Twitter's potential as a powerful marketing brand for your own benefit* Encourages you to take advantage of Twitter's vast audience Follow Me! Creating a Personal Brand with Twitter escorts you through using Twitter to create and execute a surefire personal brand marketing campaign that spans the globe.